International Labour Market Regulation and Economic Growth with Creative Destruction - Tapio Palokangas (Center for Economic Studies and ifo Institute (CESifo), 2002)
A multi-country Schumpeterian growth model is constructed when there is world-wide externality in technological knowledge. Households can enter the labour force as workers or become engineers at some cost. Production employs both workers and engineers while R&D uses only engineers. Workers are unionized and labour market regulation supports union power in wage bargaining. It is shown that international coordination of labour market policy increases the growth rate and the level of welfare. When the interest-rate elasticity of consumption in the world is low (high), the simultaneous regulation (deregulation) of the labour market in all countries increases welfare.
Keywords: 330; international technology transfers; labour market regulation; endogenous growth